Apathy Induced by Subthalamic Nucleus Deep Brain Stimulation in Parkinson's Disease: A Meta‐Analysis. Issue 2 (16th December 2020) - Zoon, Thomas J.C.; van Rooijen, Geeske; Balm, Georgina M.F.C.; Bergfeld, Isidoor O.; Daams, Joost G.; Krack, Paul; Denys, Damiaan A.J.P.; de Bie, Rob M.A.
ABSTRACT: Apathy, the loss of motivation, is a common problem in Parkinson's disease (PD) and often observed following deep brain stimulation (DBS) of the subthalamic nucleus (STN). The aim of this meta‐analysis was to determine the occurrence of apathy following STN DBS in literature. Relevant articles were searched in PubMed/Medline, SCOPUS, EMBASE, and Web of Sciences electronic databases. Studies were included if they reported apathy scores pre‐ and post‐DBS or the cross‐sectional difference between PD patients receiving STN DBS and patients receiving medication only. Thirty‐three articles were included in the meta‐analyses from 6, 658 screened articles by two authors independently. A total of 1, 286 patients were included with a mean age (±standard deviation [SD]) of 58.4 ± 8.5 years and a disease duration of 11.0 ± 5.8 years. The apathy score measured by means of the Apathy Evaluation Scale (AES), Starkstein Apathy Scale (SAS), and the Lille Apathy Rating Scale (LARS) was significantly higher after DBS than pre‐operatively (g = 0.34, 95% confidence interval [CI] = 0.19–0.48, P < 0.001). An equal, significant difference in severity of apathy was found between STN DBS and medication only (g = 0.36, 95% CI = 0.03–0.65; P = 0.004). Statistical heterogeneity was moderately high, but the effects stood strong after multiple analyses and were independent of tapering off dopaminergic medication. The findings of this meta‐analysis indicate that apathy is increased after STN DBS compared to the pre‐operative state and to medication only (systematic review registration number: PROSPERO CRD42019133932). © 2020 Universiteit van Amsterdam. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society